Use of Hybrid PEDOT:PSS/Metal Sulfide Quantum Dots for a Hole Injection Layer in Highly Efficient Green Phosphorescent Organic Light-Emitting Diodes - Zhu, Wenqing; Ding, Kuangyu; Yi, Chen; Chen, Ruilin; Wei, Bin; Huang, Lu; Li, Jun (Frontiers in Chemistry, 2021)
In this study, we have synthesized the molybdenum sulfide quantum dots (MoS2 QDs) and zinc sulfide quantum dots (ZnS QDs) and demonstrated a highly efficient green phosphorescent organic light-emitting diodes (OLED) with hybrid PEDOT:PSS/QDs hole-injection layer (HIL). The electroluminescent properties of PEDOT:PSS and hybrid HIL based devices were explored. The optimized OLED based on the PEDOT:PSS/MoS2 QDs HIL exhibits maximum current efficiency (CE) of 72.7 cd A-1, the luminance of 46354 cd m-2 and the power efficiency of 41.5 lmW-1, which shows a 28.2% higher CE as compared to counterpart which exhibits single PEDOT:PSS. The higher device performances of OLED device with hybrid HIL may be attributed to the enhanced hole injection capacity and balanced charge carrier transportation in the emissive layer. The above analysis of results illustrates an alternative way to fabricate the high efficiency OLEDs with sulfide quantum dots as HIL.